Alteration of Degree Centrality in Adolescents With Early Blindness - Wen, Zhi; Kang, Yan; Zhang, Yu; Yang, Huaguang; Xie, Baojun (Frontiers in Human Neuroscience, 2022)
Congenital nystagmus (CN) occurs in infants and young children leads to early blindness. Previous neuroimaging studies demonstrated early blindness were accompanied by structural and functional brain alterations. However, the effect impaired vision and critical developmental period on brain functional connectivity at rest remains unclear. Hence, we use the voxel-wise degree centrality (DC) method to explore the underlying functional network brain-activity in adolescents with early blindness. 21 EB and 21 SC subjects were enrolled and underwent MRI scanning. The DC method was used to assess the differences between the two groups. Moreover, support vector machine (SVM) method was applied to differentiate EB and SC, with DC value as a feature. Compared with SCs, EB patients showed increased DC in the bilateral cerebellum_6, cerebellum vermis_4_5, bilateral supplementary motor area (SMA), and left fusiform gyrus. Decreased DCs were found in the bilateral rectal gyrus and left medial orbital frontal gyrus (mOFG) in EB patients, relative to sighted control group. The SVM classification of DC values reached a total accuracy of 70.45% and area under curve of 0.86 for distinguishing the EBs and SCs. Our study may reveal the neuromachanism of neuroplasticity in EB, which provides an imaging basis for developing restoring visual therapies and sensory replacement devices (SSDs), and evaluating the effect of vision rehabilitation in future.